Closing the Gap : Gender, Transport, and Employment in Mumbai - World Bank (World Bank, Washington, DC, 2021)
Until recently, transport planning and design were regarded as gender neutral that is, they were assumed to benefit men and women equally. There is now increasing recognition that women experience mobility differently from men. This policy note, strives to improve our understanding of the specific mobility choices, needs, and experiences of women in the Greater Mumbai Region of India. It examines how the mobility patterns of men and women differ from each other, how they have evolved over time in Mumbai, and whether lack of access to mass transit has limited women’s access to jobs. Several important policy findings emerge from the note, including the need for improving public transit and walkability, and integrating the various transport modes across Mumbai. Finally, this note seeks to help policy makers in Mumbai and other cities improve the design of public transit, and the overall transportation system to better cater to the needs of female riders.